(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Sandfly breeds in soil but is selective to identify soil favourable for their breeding. Soil covered by vegetation, marshy land, orchards and settlements shows high sandfly breeding in an endemic region. Besides,the presence of inorganic constituents of the soil was found to affect sandfly breeding. Objective: To identify soil pattern in Kala-azar endemic areas suitable for sandfly breeding, and the relationship of soil’s physical and chemical properties with their breeding which may help in taking feasible measure to control the vector of Kala-azar or Visceral Leishmaniasis (VL). Materials and Methods: The cross-sectional type of descriptive study was conducted in the Kala-azar endemic areas of Trishal and Fulbaria of Mymensingh, Madhupur of Tangail and Chatmohor of Pabna district, Bangladesh during the period of July 2015 to December 2015. From each site, 250 gm soil was collected and packed in a plastic container. All the samples were taken in the laboratory and were kept as it is for one week to configure the moisture and soil temperature maintaining the lab room temp at 28±2ºC and relative humidity at 75.0%±2.0. Soil samples were analysed for physical and chemical properties at the Soil Science Department of Sher-e-Bangla Agricultural University, Dhaka. Results: Total 48 soil samples were collected from Trishal, Fulbaria, Madhupur, Chatmohor and each sample was analysed for physical property (sand, silt, clay, porosity, water content), chemical constituents (pH, C, N, Ca, Mg, K, P, Fe). The mean from each district’s soil constituents (sand, silt, clay, porosity, water content) ranged from 17.36%-18.83%, 44.10%-45.46%, 35.70%-38.06% 41.98%-47.24% respectively and among the chemical constituents, pH ranged from 7.46-7.98, Carbon 0.92-0.98 Cmolkg-1, Nitrogen 0.174-0.184 Cmolkg-1, Calcium 4.83-6.21 Cmolkg-1, Magnesium 1.97-2.46 Cmolkg-1, Potassium as K2O 1.37-1.79 Cmolkg-1, Phosphorus as P2O5 12.60-13.78 Cmolkg-1, Iron as Fe2O3 9.54-10.06 Cmolkg-1 respectively. Conclusion: Physical and chemical characteristics of soil by area of endemicity have been postulated to afford suitable environment for sandfly breeding. This information of the breeding sites of phlebotomine sandflies could help to plan environmental intervention measures that would impede the breeding of these insects. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 3-7